Biological Activities of Hydroxytriazenes and Their Iron Complexes - Choubisa, N. K.; Kodli, K. K.; Panwar, A. K.; chauhan, R. S.; Goswami, A. K. (Asian Journal of Pharmaceutical Research and Development, 2014)
The present method reports synthesis,characterization and antimicrobial activity of four hydroxytriazenes, against bacteria. All the hydroxytriazene have been Synthesized by diazo coupling reaction between diazonium salt and phenyl hydroxyl amine. The entire synthesized compounds were characterized by CHN, and IR spectra analysis. The entire synthesized compound were subjected to antimicrobial activity by zone inhibition method.